Assessment of variations in upper and lower gonial angle in children with mouth breathing habit - Saleem, Shemnidha; Belchada, Dhanya Kamalakshan; Ayilliyath, Ambili; Azhikoden, Fazila (International Journal of Clinical Trials, 2024)
Background: Mouth breathing is one of the most common deleterious oral habits in children. The habitual position of muscles inside and outside the mouth will affect dental development. Mouth breathing influences skeletal growth and thereby affects the cephalometric parameters. The present study aimed to assess if there is any variation in upper and lower gonial angles in children with mouth breathing habit. Methods: The 33 patients in the age group of 8 to 12 years reporting to the Department of Pediatric and Preventive Dentistry with chief complaint of mouth breathing was selected for the study based on inclusion and exclusion criteria. Lateral cephalograms of these children were taken with a digital panoramic system under standard exposure factors, as recommended by the manufacturer. Upper and lower gonial angles were determined on the lateral cephalograms. The values obtained were tabulated and subjected to statistical evaluation. Results: The mean upper and lower gonial angles were seen to increase from the normal in children with mouth breathing habit. However, independent sample t test showed no statistically significant difference in upper and lower gonial angles with a p value of 0.598 in upper gonial angle and 0.714 in lower gonial angle. Contusions: Early detection of the changes in the upper and lower gonial angles can help a pediatric dentist in effectively framing a treatment plan in children with mouth breathing habit, to prevent further deterioration in the dental and skeletal structures and be able to correct the already occurred unfavourable changes in them.